Endometrial Thickness Measurement for Detecting Endometrial Cancer in Women With Postmenopausal Bleeding: A Systematic Review and Meta-Analysis - Timmermans, Anne; Opmeer, Brent C.; Khan, Khalid S.; Bachmann, Lucas M.; Epstein, Elisabeth; Clark, T. Justin; Gupta, Janesh K.; Bakour, Shagaf H.; van den Bosch, Thierry; van Doorn, Helena C.; Cameron, Sharon T.; Giusa, M. Gabriella; et al. (Obstetrics and gynecology (New York. 1953), 2010)
To estimate the accuracy of endometrial thickness measurement in the detection of endometrial cancer among women with postmenopausal bleeding with individual patient data using different meta-analytic strategies. Original data sets of studies detected after reviewing the included studies of three previous reviews on this subject. An additional literature search of published articles using MEDLINE databases was preformed from January 2000 to December 2006 to identify articles reporting on endometrial carcinoma and sonographic endometrial thickness measurement in women with postmenopausal bleeding. We identified 90 studies reporting on endometrial thickness measurements and endometrial carcinoma in women with postmenopausal bleeding. We contacted 79 primary investigators to obtain the individual patient data of their reported studies, of which 13 could provide data. Data on 2,896 patients, of which 259 had carcinoma, were included. Several approaches were used in the analyses of the acquired data. First, we performed receiver operator characteristics (ROC) analysis per study, resulting in a summary area under the ROC curve (AUC) calculated as a weighted mean of AUCs from original studies. Second, individual patient data were pooled and analyzed with ROC analyses irrespective of study with standardization of distributional differences across studies using multiples of the median and by random effects logistic regression. Finally, we also used a two-stage procedure, calculating sensitivities and specificities for each study and using the bivariate random effects model to estimate summary estimates for diagnostic accuracy. This resulted in rather comparable ROC curves with AUCs varying between 0.82 and 0.84 and summary estimates for sensitivity and specificity located along these curves. These curves indicated a lower AUC than previously reported meta-analyses using conventional techniques. Previous meta-analyses on endometrial thickness measurement probably have overestimated its diagnostic accuracy in the detection of endometrial carcinoma. We advise the use of cutoff level of 3 mm for exclusion of endometrial carcinoma in women with postmenopausal bleeding.